Formation of the acicular and lamellar structure in an aluminum nitride ceramic material; Glass and Ceramics; Vol. 54, iss. 7-8 - Guzeev V. V.; Rikhvanov L. P. Leonid Petrovich; Dobrikova G. V.; Potseluev A. A. Anatoly Alekseevich (1997, 1997)
Title screen